Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Trade was also initially undermined by a severe recession. Kazakhstan is facing increased challenges from higher global commodity prices. Against this background, an encompassing policy response is needed to control inflation and mitigate the scope for second-round price effects. The increase of trade openness in the 2000s coincided with Kazakhstan becoming a major oil producer and exporter. A number of issues still need to be resolved to achieve free trade of goods and services within the borders of the union.